1991
DOI: 10.1161/01.hyp.18.6.819
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, high blood pressure, and serum gamma-glutamyl transpeptidase level.

Abstract: The influence of the level of serum y-glutamyl transpeptidase, a biological marker of alcohol consumption, on elevations of blood pressure and on the development of hypertension related to increases in alcohol consumption was determined in a cross-sectional study of 1,492 middle-aged male workers and in a subsequent 5-year follow-up study of 1,393 workers. Blood pressure levels, as well as the prevalence and incidence of hypertension, were higher in the subjects with serum y-glutamyl transpeptidase levels abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 18 publications
4
45
1
Order By: Relevance
“…In addition, as far as we know, no significant association between the volume of alcohol consumed and cytosolic-free calcium concentrations in the platelets has been confirmed in the studies on human drinkers. 26,27 A close association between serum GGT and BP in alcohol consumers was observed in the present study, and has been repeatedly shown in our previous studies [28][29][30] and in those of other researchers. 31,32 It suggested an association between hepatic manifestations induced by alcohol, mainly steatosis in the liver, and BP elevation.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, as far as we know, no significant association between the volume of alcohol consumed and cytosolic-free calcium concentrations in the platelets has been confirmed in the studies on human drinkers. 26,27 A close association between serum GGT and BP in alcohol consumers was observed in the present study, and has been repeatedly shown in our previous studies [28][29][30] and in those of other researchers. 31,32 It suggested an association between hepatic manifestations induced by alcohol, mainly steatosis in the liver, and BP elevation.…”
Section: Discussionsupporting
confidence: 89%
“…1 These results are also in agreement with previous crosssectional and longitudinal epidemiologic studies that reported a positive association between higher serum GGT level and clinical hypertension, and extend the evidence to the earlier stage of prehypertension, when primary prevention of hypertension is possible. [9][10][11][12][13][14]17 Several lines of recent evidence suggest that an association between serum GGT and hypertension is plausible, including a direct role of GGT in the generation of reactive oxygen species; an indirect role as a marker of increased extracellular catabolism of antioxidant glutathione in response to oxidative stress; its predictive relationship to future elevations in plasma F2-isoprostanes, an oxidative damage product of arachidonic acid; its relationship to markers of inflammation; and its relationship to insulin resistance and components of the metabolic syndrome. [1][2][3][4][5][6]8,9,23,24 Also, serum GGT has been shown to be associated with reduced kidney function among men without hypertension or diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 20 years, several epidemiological studies have highlighted the particular association of raised g-glutamyl transferase (gGT) and hypertension. [19][20][21][22][23][24][25] A recent prospective study has confirmed a positive association between age, serum gGT and the subsequent risk of hypertension. 26 This relationship between gGT and hypertension may be independent of alcohol consumption, where gGT has been shown to correlate with systolic and diastolic blood pressure (Table 3).…”
Section: Hypertension Metabolic Syndrome and Fatty Livermentioning
confidence: 99%